Methylphenidate use in children with attention deficit hyperactivity disorder - Machado, Felipe Salles Neves; Caetano, Sheila Cavalcante; Hounie, Ana Gabriela; Scivoletto, Sandra; Muszkat, Mauro; Gattás, Ivete Gianfaldoni; Casella, Erasmo Barbante; Andrade, Ênio Roberto de; Polanczyk, Guilherme Vanoni; Rosário, Maria Conceição do (Revista de Saúde Pública, 2015)
A Brazilian Health Technology Assessment Bulletin (BRATS) article regarding scientific evidence of the efficacy and safety of methylphenidate for treating attention deficit hyperactivity disorder (ADHD) has caused much controversy about its methods. Considering the relevance of BRATS for public health in Brazil, we critically reviewed this article by remaking the BRATS search and discussing its methods and results. Two questions were answered: did BRATS include all references available in the literature? Do the conclusions reflect the reviewed articles? The results indicate that BRATS did not include all the references from the literature on this subject and also that the proposed conclusions are different from the results of the articles chosen by the BRATS authors themselves. The articles selected by the BRATS authors showed that using methylphenidate is safe and effective. However, the BRATS final conclusion does not reflect the aforementioned and should not be used to support decisions on the use of methylphenidate.